Interview with Dr. Marta Cecilia Gutiérrez-Giraldo: Formation of teachers based on reflective practices. - Gutiérrez Giraldo, Marta Cecilia (2017)
This interview develops the teacher training approach based on reflective practices. Dra. Marta Cecilia Gutiérrez Giraldo mentions that the training of teachers should be carried out from interdisciplinary training fields that are common and based on the characteristics of the teaching staff, being that in the training of reflective teachers, educational practices are the basis on which Teachers dialogue and analyze real problems events in their classrooms and propose solutions to them. He also mentions that learning must be flexible considering students learning rhythms. She concludes by stating that emotions are essential in the teaching and learning process.